2012
DOI: 10.1111/j.1475-1313.2012.00922.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effect of lens care solutions on blink rate, ocular discomfort and visual performance

Abstract: LCSs differently affected blink rate, subjective dry eye symptoms, and visual discrimination speed. Those with wetting agents led to significantly fewer eye blinks while affording better ocular comfort for contact lens wearers, compared to that without. LCSs with wetting agents also resulted in better visual performance compared to wearing daily disposable contact lenses. These presumably are because of improved tear film quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 23 publications
(37 reference statements)
2
11
0
Order By: Relevance
“…All subjects were then asked to complete the Ocular Surface Disease Index (OSDI) questionnaire. 21,22 Clinical measurements were obtained from both eyes. When data were collected from the upper and lower eyelids for a single test, the means of these values were used unless otherwise noted, based on past findings.…”
Section: Study Visitmentioning
confidence: 99%
“…All subjects were then asked to complete the Ocular Surface Disease Index (OSDI) questionnaire. 21,22 Clinical measurements were obtained from both eyes. When data were collected from the upper and lower eyelids for a single test, the means of these values were used unless otherwise noted, based on past findings.…”
Section: Study Visitmentioning
confidence: 99%
“…Lens Care Solutions with wetting agents also resulted in better visual performance compared to wearing daily disposable contact lens. These presumably are because of the improved tear film quality [ 15 ]. One student told us about her experience in using lens care solution.…”
Section: Discussionmentioning
confidence: 99%
“…293 The wetting effect of three different lens care solutions (two care solutions with wetting agents [OPTI-FREE RepleniSH and ReNu MultiPlus] and one solution without any wetting agent [ClearCare]) on blink rate, dryness symptoms, and vision performance on 65 habitual lens wearers was studied. 318 They found that solutions with wetting agents led to significantly fewer eye blinks and better ocular comfort for contact lens wearers. Moreover, the presence of wetting agents in lens care solutions also resulted in better visual performance when compared with wearing daily disposable contact lenses.…”
Section: Care Products and Packaging Solutionsmentioning
confidence: 99%